Implementasi Program Makan Bergizi Gratis di SD Negeri Kaligandu Kota Serang - Rizki Piqria Satriani; Isti Rusdiyani; Lukman Nulhakim (CV. Creative Tugu Pena, 2026)
One of the government’s efforts to improve nutritional quality and human resources (HR) while contributing to the enhancement of the learning process in schools is the implementation of the Free Nutritious Meal Program (MBG). This study aims to examine the alignment of on-the-ground conditions such as policies, Standard Operating Procedures (SOPs), and the implementation of the Free Nutritious Meal Program (MBG) at Kaligandu Public Elementary School in Serang City. The approach used for this study is qualitative research focused on a case study. Informants, including the school principal, teachers, staff from the Nutrition Service Unit (SPPG), students, and parents, were involved in data collection methods such as observation, semi-structured interviews, and documentation. The Miles and Huberman approach was used as a reference for data analysis using the NVivo 12 software. The results of this study indicate that the MBG Program policy has been implemented in accordance with government and National Nutrition Agency guidelines to support students’ nutritional needs. The program’s Standard Operating Procedures (SOPs) cover the food distribution process, supervision, and student support during mealtime activities. However, program implementation still faces several challenges, such as delays in food distribution, food quality that does not fully meet nutritional standards, a lack of menu variety, limited supporting facilities, and an increased workload for teachers. Nevertheless, this program has had a positive impact on students’ motivation to attend school and on students who do not have time to eat breakfast at home. Therefore, ongoing evaluation and monitoring are needed to ensure that the implementation of the Free Nutritious Meals Program (MBG) runs smoothly and that its intended objectives are achieved.